Efektivitas Sosialisasi Kesehatan Terhadap Peningkatan Pengetahuan Pencegahan Hipertensi dengan Ramuan Herbal - Arribe, Edo; Pancarani, Aliffa Mutia; Porbowati, Arum; Putri, Sy. Riska Arjianti; Akbar, Muhammad Arief; Iman, Muhammad Khairul; Hasanah, Nabela Nurul; Sartika, Retno Wulan; Oktaviani, Tata Tiara; Wardhana, Wisnu; Khumaedah, Nur; Haris, Haris; Putri, Cindy Wijaya; Rizki, M. (Jurnal Pengabdian UntukMu NegeRI, 2025)
Hypertension is one of the leading causes of premature death in Indonesia, with the number of cases continuing to increase annually. Low public knowledge and persistent belief in traditional medicine myths pose challenges in hypertension prevention and control efforts. This study aims to examine the effectiveness of health education through increased herbal concoction production in improving public knowledge, attitudes, and behavior regarding hypertension prevention. The study used a quasi-experimental design with a pre- and post-test plan without a control group. The study subjects were 40 residents of Banjar Seminari Village, Dayun District, Siak Regency, selected using a purposive sampling technique. The intervention was provided through health education and hands-on practice in making herbal concoctions. Data were collected using questionnaires before and after the intervention, then analyzed using the Wilcoxon test. The results showed a significant increase in knowledge (1.2 ± 0.6 to 4.6 ± 0.5; p < 0.001), attitude (2.1 ± 0.5 to 4.3 ± 0.4; p < 0.001), and behavior (1.5 ± 0.6 to 3.8 ± 0.7; p < 0.001). Therefore, interactive education-based health socialization through herbal concoctions has been proven effective in increasing understanding, forming positive attitudes, and encouraging hypertension prevention behavior in the community.